TATA KELOLA PERUSAHAAN DAN NILAI PERUSAHAAN - CYNTHIA LAVENIA YOHENDRA; MEINIE SUSANTY (Jurnal Bisnis dan Akuntansi, 2019)
The purpose of this research is to provide empirical evidence about the influence of managerial ownership, independent board of commissioners, audit committee, institutional ownership, size, debt to equity ratio, return on equity, liquidity and dividend payout ratio on Tobin’s Q as a measure of firm value. Sample of this research are 57 non financial companies listed in Indonesia Stock Exchange and the data were selected using purposive sampling method during the research period 2014 until 2016, thus totaled 171 data. Data were analyzed using multiple regression method. The empirical evidence of this research indicated that debt to equity ratio have significant influence with negative direction of the relationship while, return on equity and dividend payout ratio have significant influence on firm value with positive direction of the relationship. Besides that, managerial ownership, independent board of commissioners, audit committee, institutional ownership, size, and liquidity have no significant influence on firm value.